1996
DOI: 10.1063/1.115584
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale magnetic MnAs particles in GaAs grown by molecular beam epitaxy

Abstract: Spherical MnAs ferromagnetic particles with controllable diameters (5–30 nm) are embedded in a high quality GaAs matrix. The particles are formed in a two step process consisting of the epitaxy of a homogeneous Ga1−xMnxAs layer at low temperatures using molecular beam epitaxy followed by phase separation upon annealing. During the annealing step, the excess arsenic in the as-grown film forms magnetic MnAs precipitates with the Mn from the Ga1−xMnxAs lattice. Structural and room-temperature magnetic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(158 citation statements)
references
References 0 publications
9
145
1
3
Order By: Relevance
“…Early work on (Ga,Mn)As (De Boeck et al, 1996) showed the low solubility of Mn and the formation of magnetic nanoclusters characteristic of many subsequent compounds and different magnetic impurities. The presence of such nanoclusters often complicates accurate determination of T C as well as of whether the compound is actually in a single phase.…”
Section: B Materials Considerationsmentioning
confidence: 99%
“…Early work on (Ga,Mn)As (De Boeck et al, 1996) showed the low solubility of Mn and the formation of magnetic nanoclusters characteristic of many subsequent compounds and different magnetic impurities. The presence of such nanoclusters often complicates accurate determination of T C as well as of whether the compound is actually in a single phase.…”
Section: B Materials Considerationsmentioning
confidence: 99%
“…These precipitates are of considerable interest in their own right: they remain ferromagnetic above room temperature, and their dimensions are typically about 30 nm in diameter [264]. An example of such a nanocrystallite precipitated in a (Ga, Mn)As matrix, imaged by TEM, is shown in Figure 22.…”
Section: Magnetic Topology Of Inhomogeneous Semiconductorsmentioning
confidence: 99%
“…Gallium arsenide (GaAs) has several properties, so it is superior to silicon for use in optoelectronic devices. Increasing attention has been paid to the preparation of diluted magnetic semiconductors (DMS), in recent years after the III-V-based DMS, such as (In, Mn)As and (Ga, Mn)As, has been successfully fabricated by low-temperature MBE [2][3][4][5]. The ferromagnetic transition temperature (T c ) has increased a little by optimal annealing study [6] in comparison with the highest reported T c ¼ 110 K.…”
Section: Introductionmentioning
confidence: 99%